Real-world clinical practice of Diabetic Foot Ulcer prevention and care in Singapore: A qualitative inquiry with healthcare professionals - Anita Pienkowska; Josip Car; James Best; Choon Huat Gerald Koh; Lorainne Tudor Car; Kavita Venkataraman; Bernhard O. Boehm; Huiling Liew; Elaine Tan; Harvinder R.S. Sidhu; Tavintharan Subramaniam; Rosalind Siah Chiew Jiat; et al. (PLoS ONE, 2025)
Aim People living with diabetes are at risk of developing diabetic foot ulcers (DFU). While international and local clinical care guidelines and pathways have been formulated to optimize the prevention and treatment of DFUs, a continuous audit of real-world adherence among healthcare professionals (HCPs) is needed to ensure care quality, safety, and efficacy. Methods A qualitative study design involving focus group discussions was used to explore practices in the prevention and treatment of DFUs. Verbatim transcripts from eight discussions involving 19 HCPs, purposively sampled, were analyzed using the framework method. Coding was guided by a DFU model of care developed from international and local clinical guidelines. Results Clinical practices for DFU prevention and care management in Singapore generally adhere to existing guidelines, though risk stratification and DFU classification are not commonly performed. During clinical visits, HCPs perform foot assessments that encompass mainly visual inspection, evaluation of vascular status and neurological status. Education on DFU prevention and management is extensive across all diabetes care. Referrals to podiatrists include cases beyond active wounds and high-risk issues. Conclusion Implications for practice are considered and highlight the need for a clearer delineation of roles among HCPs in DFU clinical care guidelines. This study provides a guide for further studies in the area of patient management.